Telogen Effluvium as a complication of scalp reconstruction with tissue expander: a case report - Di Mascio, Donatello; Sapino, Gianluca; De Maria, Federico (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The treatment of burn alopecia is still considered a challenging task for plastic surgeons. Tissue expansion has been extensively described as a useful technique used in order allow the reconstruction of large scalp defects with reliable hair-bearing tissue, enhancing the final aesthetic outcome. Case Report: We present the case of a 43-tear-old woman affected by scarring burn alopecia of left parietal area, treated with staged tissue expansion and local flap reconstruction. Despite the complete flap survival, a reversible acute hair loss 12 days after surgery, ascribable as Telogen Effluvium (TE), was reported. Conclusions: TE is a rare and self-limiting condition potentially related with any kind surgery or stressful events. Plastic surgeons should be aware of this condition, particularly when performing scalp reconstruction, as it can be misled with other local complications. Clinical diagnosis is of paramount importance to avoid useless or even harmful treatments: reassuring the patient remains the most effective therapeutic pathway.